2017
DOI: 10.1186/s12882-017-0785-1
|View full text |Cite
|
Sign up to set email alerts
|

On-line hemodiafiltration did not induce an overproduction of oxidative stress and inflammatory cytokines in intensive care unit-acute kidney injury

Abstract: BackgroundThough on-line intermittent hemodiafiltration (OL-IHDF) is a routine therapy for chronic dialysis patients, it is not yet widespread used in critically ill patients. This study was undergone to evaluate efficiency and tolerance of OL-IHDF and to appreciate inflammatory consequences of its use in intensive care unit (ICU)-acute kidney injury (AKI) patients.MethodsIn this prospective cohort study conducted in a medical academic ICU in France, 30 AKI patients who underwent OL-IHDF were included. OL-HDF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…They did not observe increase in plasmatic dosage of cytokines (IL1ß, IL4, IL6, IL8, IL10, IFN γ), growing factors ( Epidermal growth factor —EGF, Vascular Endothelial growth factor —VEGF) and MCP-1 (Macrophage Chemoattractant Protein-1). 11 We did not observe any episode of pyrogenic reaction or bacteremia during the observational period of our study. Microbiology conformity was obtained in all samples; however, a small number of treatment and samples could influence the results.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…They did not observe increase in plasmatic dosage of cytokines (IL1ß, IL4, IL6, IL8, IL10, IFN γ), growing factors ( Epidermal growth factor —EGF, Vascular Endothelial growth factor —VEGF) and MCP-1 (Macrophage Chemoattractant Protein-1). 11 We did not observe any episode of pyrogenic reaction or bacteremia during the observational period of our study. Microbiology conformity was obtained in all samples; however, a small number of treatment and samples could influence the results.…”
Section: Discussionmentioning
confidence: 54%
“…20 Klouche et al observed similar rates from percentage reduction from Cystatin C and β-2 microglobulin in critically ill patients with AKI who underwent an on-line HDF: 44.5% and 51.5%, respectively. 11 Removal of middle molecules is higher in HDF compared with high flux IHD, 2022 however, a target was not established for blood levels reduction of these substances in patients with AKI.…”
Section: Discussionmentioning
confidence: 99%
“…IL-4 is an anti-inflammatory factor that belongs to the interleukin family [19]. It has been reported that IL4 can inhibit apoptosis of liver cancer cells, and blockage of the IL4/IL4R/STAT6 axis can promote apoptosis of Hodgkin lymphoma cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, little is known about the oxidative status in patients under OL-HDF. Klouche et al recently described that inflammation is not affected by OL-HDF and that advanced oxidation protein products are reduced in the process [46]. This would lead to an attenuation in oxidative stress in these patients, which could contribute to their improved survival.…”
Section: Discussionmentioning
confidence: 99%